Socialisation and Human Rights Education in Schools (Journal of Parents and Teachers, 2026)
European conference on socialisation and human rights education, showcasing experiences from three countries. The conference examines solidarity initiatives, research into moral development and school practices that run counter to democratic values.
Keywords: Democracy; values; moral development; curriculum; citizenship